Measuring early child development in low and middle income countries: Investigating the validity of the early Human Capability Index - Alanna Sincovich; Tess Gregory; Cristian Zanon; Daniel D. Santos; John Lynch; Sally A. Brinkman (Elsevier, 2020)
Inclusion of early child development in the United Nations Sustainable Development Agenda raises issues of how this goal should be monitored, particularly in low resource settings. The aim of this paper was to explore the validity of the early Human Capability Index (eHCI); a population measure designed to capture the holistic development of children aged 3-5 years. Convergent, divergent, discriminant and concurrent validity were examined by exploring the associations between eHCI domains and child (sex, age, stunting status, preschool attendance) and family (maternal education, home learning environment) characteristics. Analyses were repeated using data from seven low and middle income countries: Brazil (n = 1810), China (n = 11421), Kiribati (n = 8339), Lao PDR (n = 7493), Samoa (n = 12191), Tonga (n = 6214), and Tuvalu (n = 549). Correlations and linear regressions provide evidence that within these country samples, the tool is capturing the aspects of early child development that it was designed to measure. Although the tool was intended to measure development of children aged 3-5 years, results suggest it can be validly applied to children aged 2-6 years. The eHCI is free, requires minimal implementation resources, captures development across domains and abilities, and is designed to allow cultural and contextual concepts to be included. The eHCI appears psychometrically robust in diverse country contexts and could enable evaluation of early years policies and programs, as well as monitoring of children's development to track progress towards the Sustainable Development Agenda.